Psychopathy and Recognition of Facial Expressions of Emotions:: A Systematic Review - Lemos Vasconcellos, Silvio José (2014)
Psychopathy is a personality disorder characterized by anti-social behavior, compromised judgment and deficitsof emotional processing. Researchers have been investigating the ability of psychopaths and individuals with psychopathic traitsto recognize emotions expressed through the face. The present study performed a systematic review using the main internationaldatabases of articles about this theme, published between 1975 and 2013. Seventeen articles fulfilled the inclusion criteria ofthis review. The results evidenced the use of non-converging methods and suggest that psychopathy is related to deficits inrecognition of negative feelings. Confirmatory data can only be achieved through a methodological standardization. In futurestudies the use of distinct stimuli exposure time is suggested.